Randomized greedy algorithm for helicopter optimization in the energy industry: a practical approach to model development and solution deliverance - Navarre, Jeremy T (International journal of energy sector management, 2022)
Purpose The global energy industry transports supplies and personnel via helicopter to offshore locations and is increasingly focusing on optimizing upstream logistics. This paper aims to and achieves a mutually beneficial balance between research and practice by providing generalizable methods to a problem routinely encountered in practice. Overall, the development and execution of the heterogeneous capacitated helicopter routing problem with split deliveries and multiple depots is validated by the networks’ results. Design/methodology/approach Using a unique sample of deepwater and ultra-deepwater permanent offshore locations in the Gulf of Mexico, transportation networks consisting of 57 locations operated by 19 firms are optimized via a randomized greedy algorithm. The study’s randomized greedy algorithm yields depot assignment, vehicle assignment, passenger assignment and routing. All data processing techniques and iterative algorithm processes are defined and explained. Findings Results show that the model effectively solves the complex transportation networks consisting of subject firms’ offshore nodes and eligible depots. Specifically, average load factors related to seat capacity and effective vehicle capacity of 87.7 and 95.7% are realized, respectively. The study’s model is a unique contribution to the extant literature and provides researchers and practitioners a practical approach to model development and solution deliverance. Research limitations/implications The extant literature encompasses works that inadequately observe the complexity associated with the transportation of personnel. Specifically, this research, unlike many works in the extant literature, uses a heterogeneous versus homogeneous fleet, includes multiple depots versus a single depot and allows split deliveries. Also, the current research ensures all relevant aircraft capabilities and limitations are observed. In particular, the paper takes into account vehicles’ seat capacities, effective capacities via maximum gross takeoff weights and reserve fuel requirements. The current model, which is built upon a heterogeneous capacitated helicopter routing problem with split deliveries and multiple depots (HCHRPSDMD), sufficiently provides a practical approach to model development and solution deliverance while promoting future research endeavors. Future research may use these findings for other geographical regions and similar transportation networks and could adopt firm-specific actual cost parameters instead of the estimated average hourly costs of operating different helicopters. Furthermore, future endeavors may employ other techniques for the derivation of solutions. Future works may be enhanced with actual cost data in lieu of estimations. In the current study, cost data were not available; however, estimations do not inherently proscribe sound interpretations of the models’ outputs. Also, future research endeavors including manual method results may enable comparative results to establish cost variance analysis. Although the current study is, to some extent, limited, the practicality for practitioners and contribution to researchers is comprehensible. Due to the idiosyncrasies and complexity prevalent in modern transportation networks, optimization is and will continue to be a rich opportunity for implementation and research. Practical implications As described by previous researchers, energy firms may more efficiently use their contracted aircraft via implementation of a decision-making mechanism for passenger assignment, aircraft selection, depot selection and aircraft routing. Most energy firms possess numerous and spatially segregated offshore facilities and, therefore, are unable to efficiently and effectively make such decisions. Ultimately, the efficient use of firms’ contracted helicopters can enhance profitability via reduced costs without compromising operational performance. Reduced costs are likely to be realized by a potential workforce or workload reduction, reduced flight hours and enhanced bargaining power with commercial helicopter operators. Specifically, enhanced bargaining power may be realized as a result of minimized depots from which the aircraft are operated and an overall reduction of aircraft via increased asset utilization. In essence, the efficient use of commercial helicopters may yield systemic efficiencies that can be shared among all stakeholders, contracting energy firms and commercial helicopter operators. The achievement of operational efficiencies, ultimately, may determine the realization of target performance or solvency of a plethora of firms in the future (Krishnan et al., 2019). Social implications For economies, communities and industries depending on crude oil and natural gas production, people’s livelihoods are significantly impacted due to price fluctuations (Rostan and Rostan, 2020; Solaymani, 2019). Based on a unique set of inputs and outputs, the International Energy Agency region (IEA), which includes the current study’s sample set, was found to achieve greater overall production efficiency relative to the Organization of the Petroleum Exporting Countries (OPEC) and the Organization of Arab Petroleum Exporting Countries (OAPEC) (Ohene-Asare et al., 2018). Therefore, enhanced logistics efficiency within the energy industry’s transportation sector across the globe is reasonably likely. For countries relying on these commodities’ exportation, production efficiency is and will continue to be a priority. With limited resources available in industry and society, efficiency is prone to yield advantageous results for all stakeholders. Furthermore, in the context of this study, a reduction of carbon dioxide and noise pollution in air, above water and on land will contribute to society’s drive to protect the environment and preserve our natural resources for future generations. Originality/value The current study represents the lone or one of few research endeavors to evaluate the heterogeneous capacitated helicopter routing problem with split deliveries and multiple depots. Furthermore, research pertaining to transportation via helicopter in the Gulf of Mexico’s offshore basin is unprecedented. Lastly, this work yields actionable knowledge for practitioners while enhancing current and promoting future research endeavors.